Study on electrochemical corrosion behavior of gray cast iron processed via laser cavitation peening - Chunhui Luo; Jiayang Gu; Jiahao Yang; Yanfen Sun; Yuwen Ding; Aihua Xu; Xiaohu Sang (PLoS ONE, 2026)
Laser cavitation peening (LCP) is a novel material surface treatment method. In this study, we investigated the electrochemical corrosion performance of LCP-treated HT250 gray cast iron, with and without a coverage layer, under various laser energies, defocusing amounts, and immersion times. In the LCP process, a 0.04 mm aluminum coverage layer was employed. The influence of the coverage layer on LCP processing was analyzed. The results show that the presence of a coverage layer during the LCP treatment improves the specimen’s anti-corrosion ability, with this alignment corresponding with an increase in laser energy. In comparison with laser energy, the effect of a coverage layer on corrosion resistance at various defocusing amounts is not very significant, and at a smaller defocusing amount, the treated specimen presents higher corrosion resistance. The corrosion resistance of gray cast iron in the case with a coverage layer first increases with the increase in laser energy and then decreases. The presence of a coverage layer helps to avoid laser ablation and cavitation erosion.